Multi-stacks of epitaxial GeSn self-assembled dots in Si: Structural analysis - Oliveira, F.; Fischer, I. A.; Benedetti, Alessandro; Cerqueira, M. F.; Vasilevskiy, M. I.; Stefanov, Stefan K; Chiussi, Stefano; Schulze, J. (Journal of Applied Physics, 2015)
We report on the growth and structural and morphologic characterization of stacked layers of self-assembled GeSn dots grown on Si (100) substrates by molecular beam epitaxy at low substrate temperature T = 350°C. Samples consist of layers (from 1 up to 10) of Ge0.96Sn0.04 self-assembled dots separated by Si spacer layers, 10nm thick. Their structural analysis was performed based on transmission electron microscopy, atomic force microscopy, and Raman scattering. We found that up to 4 stacks of dots could be grown with good dot layer homogeneity, making the GeSn dots interesting candidates for optoelectronic device applications.
CRIS-Team Scopus Importer:2021-06-29